A Petrochronological Investigation of Metamorphic, Melt and Fluid Related Processes in Lower Crustal Rocks from Southwestern Norway and Southern India - Blereau, Eleanore Renee (Curtin, 2017)
A petrochronological approach permitted quantitative constraints on the duration, conditions and spatio-temporal controls on metamorphism within complex high-grade metamorphic terranes. The effects of prolonged high temperatures on commonly used geochronometers, zircon and monazite, contrasts between terranes. The availability of these minerals and information recorded in lower crustal rocks is highly controlled by lower crustal processes, but the involvement of particular processes is resolvable through the integration of many analytical techniques into a coherent multidisciplinary interpretation.